Status of Conditions and Identification of Damage to Seagrass Beds in the Waters of South Kayoa District, South Halmahera Regency - M Said Alhaddad; Adi Noman Susanto; Fajria Dewi Salim (Jurnal Biologi Tropis, 2022)
The study of condition status and identification of problems of seagrass damage in the waters of South Kayoa District, South Halmahera Regency aims to determine the status of seagrass ecosystem conditions and identify problems of seagrass ecosystem damage in the waters of South Kayoa District, South Halmahera Regency. Based on the research results on the status of the level of damage to the seagrass ecosystem in the waters of the South Kayoa District, South Halmahera Regency, about the Decree of the Minister of State for the Environment no. 200 of 2004. The station I (Pasir Putih) has an area of ​​61.23 significant damage. Station II (Ngute-Ngute) damage area 49.69 moderate damage. Station III (Posi-Posi) has an area of ​​39 moderate damage. Station IV (Sagaole) Damage area 46.90 moderate damage. Station V (Pass), with an area of ​​60.28, is under significant damage. While the factors causing the seagrass damage were identified due to natural factors in the form of waves and human factors in the form of ship/boat mooring, ship/boat anchorage, breakwater construction, resident settlements, dock construction, Doro (road opening in the seagrass area), construction of public roads, fishing fish and non-fish and seaweed cultivation.